2019
DOI: 10.21037/atm.2019.11.142
|View full text |Cite
|
Sign up to set email alerts
|

International expert consensus on the management of bleeding during VATS lung surgery

Abstract: Intraoperative bleeding is the most crucial safety concern of video-assisted thoracic surgery (VATS) for a major pulmonary resection. Despite the advances in surgical techniques and devices, intraoperative bleeding is still not rare and remains the most common and potentially fatal cause of conversion from VATS to open thoracotomy. Therefore, to guide the clinical practice of VATS lung surgery, we proposed the International Interest Group on Bleeding during VATS Lung Surgery with 65

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 58 publications
(88 reference statements)
0
33
0
Order By: Relevance
“…Importantly, these events were self-limiting. Major complications observed were assessed as not related to the treatment or device, instead reflecting the known complications of surgical lobectomy (persistent air leak is reported in 10% of patients following VATS lobectomy [13], major vascular injury in 3–8% [14, 15]).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these events were self-limiting. Major complications observed were assessed as not related to the treatment or device, instead reflecting the known complications of surgical lobectomy (persistent air leak is reported in 10% of patients following VATS lobectomy [13], major vascular injury in 3–8% [14, 15]).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preventive clamping can reduce pulmonary artery pressure, which may facilitate lymph node dissection-for lymph nodes or tumors with severe adhesions to blood vessels, pulmonary artery clamping can facilitate a difficult dissection [20,21]. Also, the reduced tension in the distal pulmonary artery greatly lowers the risk of pulmonary artery rupture during dissection [20,21]. Even if the pulmonary artery ruptures during dissection, no major bleeding will occur, and the repair can be unhurried.…”
Section: Discussionmentioning
confidence: 99%
“…This clamping technique occupies very minimal space with simple instrumentation [ 8 – 10 ], providing sufficient operating space for pulmonary artery repair and minimizes instrumentation interference. In addition, preventive clamping can reduce pulmonary artery pressure, which may facilitate lymph node dissection—for lymph nodes or tumors with severe adhesions to blood vessels, pulmonary artery clamping can facilitate a difficult dissection [ 20 , 21 ]. Also, the reduced tension in the distal pulmonary artery greatly lowers the risk of pulmonary artery rupture during dissection [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the minimal invasion associated with VATS its use in treating early-stage NSCLC has increased over years (8)(9)(10)(11)(12), and studies have demonstrated the advantages of VATS compared with open thoracotomy, including a lower morbidity rate (8,(13)(14)(15), shorter chest tube duration (13,14), less intraoperative blood loss (14), and shorter postoperative hospital stay (8,(13)(14)(15)(16)(17). However, the surgical skills of VATS need practice and training and there is potential risk of uncontrollable bleeding by VATS (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%